10.28 CULTURE AND PHILOSOPHICAL THOUGHTS IN CENTRAL ASIA - Salimov Bakhriddin Lutfullaevich. Associate Professor of TDTr.U. Jumaniyazova Nasiba Saparbaevna. Senior teacher of TDTr.U. Islomova Madina Ilhom qizi. Student of TDTr.U. (Innovative technologies in construction Scientific Journal, 2024)
It was carried out on the basis of the spirituality, politics, ideology, art of words and speech of that time. With the improvement of the labor process, artistic speech and written works also appeared, without which the people’s lifestyle could not develop. People have developed the skills to characterize and describe life experiences, natural and social phenomena through images. Key words: Culture, art, literature, philosophy, thought. It would not be wrong to say that the art of artistic words is the oldest among the arts. Speech, considered a gift of God to man, had a perfect character even in ancient times. It was carried out on the basis of the spirituality, politics, ideology, art of words and speech of that time. With the improvement of the labor process, artistic speech and written works also appeared, without which the people’s lifestyle could not develop. People have developed the skills to characterize and describe life experiences, natural and social phenomena through images. As a result, various industries have developed based on lifestyle. In conclusion, before writing and written literature, oral creativity appeared and caused written literature to appear. Some of the sources of the oral literature of the peoples of Central Asia have come down to us. Examples of these are the works of Herodotus, Ctesius, Poliene, Hares Mytelensky and other scholars. Samples of Central Asian folk art have been recorded in their works.